BS ENISO 11806-2. Agricultural and forestry machinery. Safety requirements and testing for portable, hand-held, powered brush-cutters and grass-trimmers. Part 2. Machines for use with back-pack power unit (23rd June 2020) - British Standards Institution,
No abstract available